AN UNUSUAL SITE FOR THYROID CANCER: A CASE REPORT ON ECTOPIC PAPILLARY THYROID CARCINOMA - Yee, Yoh Yee; Ci, Goh Qing; Nee, Low Yen; Voon, Tong Chin (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Ectopic thyroid tissue is rare, and the prevalence of ectopic thyroid cancer is even rarer. We report the case of a 37-year-old female with ectopic papillary thyroid carcinoma. CASE A 37-year-old female initially presented to the Ear, Nose and Throat (ENT) clinic with a midline upper anterior neck swelling that had gradually increased in size over several months. She did not complain of any compressive or infective symptoms. A computed tomography scan of the neck showed ectopic thyroid at the lingual area, thyroglossal cyst at the hyoid level, posterior to the thyroglossal cyst, and left supraclavicular locations. Fine needle aspiration for cytology) of the left supraclavicular swelling was reported as papillary thyroid carcinoma. Subsequent thyroid scintigraphy further confirmed the presence of ectopic thyroid tissue or foci of metastasis. Pre-surgery blood investigation showed Free T4 of 13.4 pmol/L (11-22), TSH of 4.042 mIU/l, unstimulated thyroglobulin of >300 mcg/L (2—50 mcg/L), and negative anti-thyroglobulin. The patient underwent bilateral neck dissection, Sistrunk procedure, and ablation of the base of the neck. Histopathology showed ectopic thyroid tissue with papillary thyroid carcinoma from the Sistrunk specimen and bilateral lymph node metastases. Thereafter, she underwent radioiodine ablative therapy with 100 mCI of Iodine-131. Serial whole-body scans showed physiologic findings. Currently, she is on TSH suppression therapy and close monitoring for tumor recurrence. CONCLUSION This case is a reminder of the embryological journey of thyroid tissue, defects of which can lead to its ectopic location. In spite of its rarity, thyroid carcinoma can occur in ectopic thyroid tissue.